Perancangan tas multifungsi sebagai sarana display peralatan doodling Komunitas DAT - Kirana Rahman; Ghia Tri Jayanti; Handayani Madania Insani (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
This research is based on problems faced by the Doodle Art Tasikmalaya (DAT) Community regarding the efficient management of communal doodling equipment during routine meet-ups. The main issue lies in the equipment organization system that is often disorganized, difficult to reach, thus disrupting the comfort of the tables used by the community in cafés. The results of these observations became the basis for this research which used mixed method with Double Diamond as a framework consisting of four stages: Discover, Define, Develop, and Deliver. In the Develop stage, the PMI (Plus, Minus, Interesting) method was used for the ideation filtering process. Qualitative data were collected through field observations and interviews, while quantitative data were collected through questionnaires distributed to community members to map the characteristics of DAT members. The result of this research is a prototype of a multifunctional bag that functions as a storage place and a display medium for communal doodling equipment owned by the community. Based on the trial results, the product structure was able to support a total load of 1.28 kg of doodling equipment without showing any defects or structural deformation, both in display and carry modes. These findings indicate that the product effectively addresses the problems faced by the DAT community regarding the efficient storage and display of doodling equipment through a single integrated product.Published Date: 2026-07-22